Origin and expression of the cusp of Carabelli in different ethnic groups from southwestern Colombia: A documentary study (Revista Nacional de Odontología, 2017)
Introduction: the objective of this research was to determine the frequency and variability of Carabelli Cusp in the first permanent molars nine contemporary ethnic groups in southwestern Colombia.Materials and Methods: This cross-sectional observational study that used the information available on the cusp of Carabelli in two studies seven databases, to design a distance matrix with the respective dendrogram and establish the biological distances between different ethnic groups.Results: It was observed that the dental morphological trait is considered absent in ethnic groups considered, except for the Afro-Colombian town of Tumaco. It was possible to show that the Nasa indigenous expressions have high minimum cusp fosomorfas and expressions, while the Caucasoid mestizos and Afro-Colombians have relatively high frequencies of cusp expressions. The distance matrix allowed noting there is a tendency of populations in southwestern Colombia to partner with the level of mixing and the origin and influence Mongoloid, Caucasoid and Negroid.Conclusions: The association of ethnic groups does not correspond to three dental complex world; however, to include in this analysis different world populations was observed than Caucasian mestizos Cali African descendants in Puerto Tejada and Nasa indigenous associated with Mongoloid populations, while people of African descent in Villarica, Guapi and Tumaco were associated with Caucasoid populations. The cusp of Carabelli not alone constituted discriminator contemporary ethnic groups in southwestern Colombia.
Keywords: dental anthropology; cusp of Carabelli; ethnic groups from southwestern Colombia; dental morphology